ARGUMENTOS PARA LA LIBERTAD - Escalante, Andrés A. (2020)
Arguments for Liberty is a compilation of essays written by nine renowned academic philosophers, on political freedom, as a just and moral system. Ideas are developed in this sense and neatly making use of Kantian, Objectivist, Rawlsian and morally pluralistic arguments. This book is important for at least two reasons. The first is because freedom matters. The second reason is because philosophy also matters, perhaps to defend freedom.